Global liquidity: Drivers, volatility and toolkits - Linda S. Goldberg (Federal Reserve Bank of New York, 2023)
Global liquidity refers to the volumes of financial flows-largely intermediated through global banks and non-bank financial institutions-that can move at relatively high frequencies across borders. The amplitude of responses to global conditions like risk sentiment, discussed in the context of the global financial cycle, depends on the characteristics and vulnerabilities of the institutions providing funding flows. Evidence from across empirical approaches and using granular data provides policy-relevant lessons. International spillovers of monetary policy and risk sentiment through global liquidity evolve in response to regulation, the characteristics of financial institutions, and actions of official institutions around liquidity provision. Strong prudential policies in the home countries of global banks and official facilities reduce funding strains during stress events. Country-specific policy challenges, summarized by the monetary and financial trilemmas, are partially alleviated. However, risk migration across types of financial intermediaries underscores the importance of advancing regulatory agendas related to non-bank financial institutions.
Keywords: E44; F30; G15; G18; G23; 330; global liquidity; global dollar cycle; trilemma; exchange market pressure; risk sensitivity; safehaven; capital flows; non-bank financial intermediaries; risk migration; Internationale Liquidität; Internationaler Finanzmarkt; Internationale Bank; Finanzmarktaufsicht; Internationaler Kredit; Kreditgeschäft; Kapitalmobilität; Geldpolitik; Risikopräferenz; Spillover-Effekt; Finanzkrise; Welt